Environmental Perceptions, Cognitions and Attitudes - Cut Sarha Airlangga; Khoirul Jismi Fajar; Muhammad Farhan Ghani (PT. Anagata Sembagi Education, 2024)
This article discusses the important aspects highlighted including psychophysics, perception, attitudes, and the relationship between humans and the environment. Psychophysics emphasizes the importance of the relationship between physical stimulus and subjective response, with the growth of the nervous system, muscles, and changes in physical structure playing a role in psychophysical development. Perception is a key process in understanding the environment, which is influenced by theories such as classical conditioning, instrumental, and social learning. Attitudes, as evaluations of objects, are influenced by mental readiness, mental organization, behavioral direction, and behavioral drivers. Humans and their environment have an interdependent relationship, where human attitudes and behaviors can affect the quality of the environment and their own quality of life. Therefore, understanding the interaction between psychological and physical aspects is essential to understanding how humans respond to and interact with their environment.